REVITALISASI LEMBAGA PENDIDIKAN ISLAM DALAM TRANSISI DARI TRADISI KE TRANSFORMASI DI ERA GLOBAL: (Revitalization of Islamic Educational Institutions in the Transition from Tradition to Transformation in the Global Era) - Rahmi Nur Azizah; Muhammad Firdaus; M. Yakub (Raqib: Jurnal Studi Islam, 2025)
This article explores the revitalization of Islamic educational institutions in the context of transitioning from tradition to transformation in the global era. The main focus is on the urgency of institutional reform, the strategic role of Islamic education, and adaptive strategies that integrate Islamic values with modern demands. Using a qualitative approach based on literature review, the study examines fundamental concepts of Islamic education institutions, their types and roles, as well as current challenges, including resistance to innovation, managerial limitations, and human resource capacity. The findings reveal that revitalization is not merely a structural necessity but also a value-based imperative, requiring Islamic institutions to act as agents of spiritual-based social transformation. The article proposes several key strategies, including institutional management reform, enhancement of educators’ competencies, and cross-sectoral collaboration. In conclusion, successful revitalization must be holistic and participatory to ensure that Islamic educational institutions remain relevant and competitive in shaping a future-oriented generation in the global landscape.